2009
DOI: 10.1111/j.1460-9568.2008.06591.x
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone reverses 17β‐estradiol‐mediated neuroprotection and BDNF induction in cultured hippocampal slices

Abstract: Due to the many similarities in mechanisms of action, targets and effects, progesterone, estrogen and neurotrophins have been implicated in synaptic plasticity as well as in neuroprotection and neurodegeneration. In this study, we examined the interactions between 17-β-estradiol (E2) and progesterone (P4) and BDNF on both plasticity and excitotoxicity in rat cultured hippocampal slices. First, we evaluated the neuroprotective effects of E2 and P4 against NMDA toxicity in cultured rat hippocampal slices. As pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
75
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 38 publications
3
75
1
Order By: Relevance
“…Moreover, the effects of endogenous PRG were not detected in guinea pigs that were treated with a high dose of βE 2 B (15). These results suggest that βE 2 antagonizes the effects of PRG on CBF in the fimbria. Some reports have shown that PRG signaling antagonizes or interacts with βE 2 signaling.…”
Section: Animals and Treatmentsmentioning
confidence: 64%
See 4 more Smart Citations
“…Moreover, the effects of endogenous PRG were not detected in guinea pigs that were treated with a high dose of βE 2 B (15). These results suggest that βE 2 antagonizes the effects of PRG on CBF in the fimbria. Some reports have shown that PRG signaling antagonizes or interacts with βE 2 signaling.…”
Section: Animals and Treatmentsmentioning
confidence: 64%
“…The beating cilia of the Fallopian tube in guinea pigs at 4 weeks of age are unlikely to be affected by βE 2 and PRG, because the ovulation starts at 8 weeks of age in guinea pigs. In the fimbria from 4-week-old guinea pigs, CBF was high (17.8 ± 0.2 Hz, n = 3) (Fig.…”
Section: Interactions Between βE 2 and Prgmentioning
confidence: 99%
See 3 more Smart Citations